Telaah Ayat Al-Qur'an Tentang Dasar-Dasar Hukum Tata Negara Dalam Konteks Kebijakan Publik - Zamzamy, Farhan A’la (Menara Tebuireng, 2025)
This article discusses the influence of constitutional law in the formation of state policy, with a focus on the application of values ​​contained in the Qur'an. This study examines how the principles of the Qur'an, such as amanah, justice, and deliberation, can be integrated into the framework of modern constitutional law to create public policies that are fair and beneficial to society. The principle of amanah teaches that power must be used with full responsibility and trust from the people, while the principle of justice demands policies that serve all levels of society equally and without discrimination. In addition, the application of deliberation, as taught in QS. Ash-Shura: 38, reinforces the importance of people's participation in the decision-making process. This article also highlights the challenges in implementing these principles, such as political pressure and conflicts of interest, as well as the importance of maintaining integrity and transparency in public policy. By integrating the values ​​of the Qur'an, it is hoped that leaders can make policies that are not only legally valid, but also ethical and reflect social justice. Through this study, it is hoped that a deeper understanding of the relationship between constitutional law, public policy, and the values ​​of the Qur'an can encourage the creation of a more trustworthy, just, and welfare-oriented government. This article aims to provide guidance for policy makers in formulating policies that are in line with Islamic moral and legal principles.